The Effect of CpG Sequences on Capsid-Specific CD8(+) T Cell Responses to AAV Vector Gene Transfer - Xiang, ZhiQuan (Mol Ther, 2020)
Transfer of genes by adeno-associated virus (AAV) vectors is benefiting patients with particular genetic defects. Challenges remain by rejection of AAV-transduced cells, which may be caused by CD8(+) T lymphocytes directed to AAV capsid antigens. Reducing the number of CpG motifs from the genome of AAV vectors reduces expansion of naive T cells directed against an epitope within the capsid. In contrast, AAV capsid-specific memory CD8(+) T cells respond more vigorously to AAV vectors lacking CpG motifs than to those with CpG motifs presumably reflecting dampening of T cell expansion by cytokines from the innate immune system. Depending on the purification method, AAV vector preparations can contain substantial amounts of empty AAV particles that failed to package the genome. Others have used empty particles as decoys to AAV-neutralizing antibodies. We tested if empty AAV vectors given alone or mixed with genome-containing AAV vectors induce proliferation of naive or memory CD8(+) T cells directed to an antigen within an AAV capsid. Naive CD8(+) T cells failed to respond to empty AAV vectors, which in contrast induced expansion of AAV-specific memory CD8(+) T cells.